2023
DOI: 10.1021/acs.nanolett.3c01454
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Site Synergistic Effects of Dual-Atom Nanozyme Enhances Peroxidase-like Properties

Abstract: Pursuing effective and generalized strategies for modulating the electronic structures of atomically dispersed nanozymes with remarkable catalytic performance is exceptionally attractive yet challenging. Herein, we developed a facile “formamide condensation and carbonization” strategy to fabricate a library of single-atom (M1-NC; 6 types) and dual-atom (M1/M2-NC; 13 types) metal-nitrogen-carbon nanozymes (M = Fe, Co, Ni, Mn, Ru, Cu) to reveal peroxidase- (POD-) like activities. The Fe1Co1-NC dual-atom nanozyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Song's group further illuminated the synergistic effect observed in Fe 1 Co 1 –NC dual-atom POD-like nanozymes. 91 This work revealed that the incorporation of heteronuclear metal sites induced electronic structure modulation and optimized H 2 O 2 substrate adsorption (Fig. 6d).…”
Section: Practical Applications Of Dacs In Nanozymesmentioning
confidence: 73%
See 1 more Smart Citation
“…Song's group further illuminated the synergistic effect observed in Fe 1 Co 1 –NC dual-atom POD-like nanozymes. 91 This work revealed that the incorporation of heteronuclear metal sites induced electronic structure modulation and optimized H 2 O 2 substrate adsorption (Fig. 6d).…”
Section: Practical Applications Of Dacs In Nanozymesmentioning
confidence: 73%
“…5d). 91 The Fe 1 Co 1 –NC dual-atom nanozyme with Fe 1 –N 4 /Co 1 –N 4 coordination exhibited remarkable enhancement of POD-like catalytic properties and excellent photothermal conversion efficiency. Wei's group presented a facile approach for crafting Zn/Mo dual atomic-based SAzymes (Zn/Mo DSAC–SMA) via the assembly of supramolecular coordination complexes and polyoxometalates (Fig.…”
Section: Practical Applications Of Dacs In Nanozymesmentioning
confidence: 96%
“…35–37 Meanwhile, two characteristic peaks occurred at 653.96 and 642.56 eV, attributed to the Mn 2p 3/2 and Mn 2p 1/2 spin orbitals of MnO 2 , respectively. 38–40 Notably, the appearance of the N 1s peak correlates with BSA.…”
Section: Resultsmentioning
confidence: 98%
“…In recent years, with the advancement of nanotechnology and diagnostic techniques, different signal transduction strategies based on nanomaterials are playing a great role in biomolecular diagnostics such as electrochemical methods, photoelectrochemical methods, fluorescence methods, piezoresistive sensing, etc. [7][8][9][10][11][12] Among various techniques, classical electrochemical analysis, developed by integrating electronic signalers/converters and identifiers, has gained a unique role in the field of analytical detection due to the obvious advantages of great sensitivity, fast response, ease of operation, and compactness. [13][14][15] In the last few decades, a large number of electrochemical sensors have been successfully designed and developed as powerful tools to interrogate the expression levels of target objects ranging from ions to disease biomarkers, pesticides, and biotoxins in real samples.…”
Section: Introductionmentioning
confidence: 99%